Cation‐tunable blue phosphor Ca2PO4Cl:Eu2+: enhancive emission and site occupancy. (11th September 2015) - Chen, Wanping; Zhou, Ahong
Abstract: A series of blue phosphors Ca1.98– x Mx PO4 Cl:0.02Eu 2+ ( M  = Mg and Sr) with different values of x were synthesized using a high‐temperature solid‐state reaction. X‐Ray diffraction and photoluminescence measurements were used to study the phase structure and luminescence properties. Ca2 PO4 Cl:0.02Eu 2+ exhibits a tunable emission intensity and color due to the incorporation of Sr 2+ or Mg 2+ . The incorporation of Sr 2+ reduces the luminescence intensity and results in a slight red shift in the emission band. The incorporation of Mg 2+ results in enhanced emission and a clear blue shift in the emission band along with a tunable chromatic coordination. Under excitation at λ  = 334 nm, the emission intensity of the Mg 2+ ‐doped Ca2 PO4 Cl:0.02Eu 2+ is found to be 250% that of Ca2 PO4 Cl:0.02Eu 2+ . The luminescence behaviors of the as‐synthesized phosphors are discussed according to the host crystal structure and site occupancy of Eu 2+ . The results indicate that Mg 2+ ‐doped Ca2 PO4 Cl:Eu 2+ is more applicable as a near‐UV‐convertible blue phosphor for white light‐emitting diodes. Copyright © 2015 John Wiley & Sons, Ltd.